THE IMPACT OF MEASURING CUSTOMER PROFITABILITY ON COST MANAGEMENT - CASE STUDY IN AL NARJIS CONTRACTING AND GENERAL TRADING COMPANY (World Economics and Finance Bulletin, 2024)
This research aims to evaluate the usefulness of measuring customer profitability in cost management through a literature review and a case study in Al-Nargis Contracting and General Trading Company